Studi Eksperimen Metode Mengajar Resipocal Self Check Terhadap Peningkatan Kemampuan Tenis Lapangan - Syaiful, Andi; Widyanto, Zainal; Marsuki, Marsuki (STAMINA, 2023)
methods, which may be expected to be used as alternative models of solutions in the context of developing the quality of learning the game of tennis. The method used is an experimental method using the Pretest Posttest Control Group Design, in this design the sample is obtained for the total population, then an initial test or pre-test is held. The initial test was carried out to determine the initial ability of the sample, in this case the ability to play tennis. The data from the initial test results are arranged based on ranking, the aim is to determine the ability of playing tennis skills, samples ranging from the largest to the lowest. Then divided into two, then two objects that have the same score are matched using the maching method so that there are two groups that have almost the same tennis playing skills. The analysis used in this study is the t test which has fulfilled the homogeneous requirements and is normally distributed, based on the calculation results, it is known that the value of t = 2.42 > t table = 2.201, with a level of = 0.05. So it can be concluded that the reciprocal teaching method is more influential than the self-check method.